Construction and validation of educational booklets regarding oral antineoplastics - Andrieli Meira COSTA; Miriane Regina MOURA; Antônio Matoso MENDES; Camile ROCHA (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2024)
Objective: To construct and validate educational pamphlets on oral antineoplastic therapy for patients with oncologic or hematologic diseases treated on an outpatient basis. Method: We carried out this research on two stages: a) Elaboration of educational pamphlets by the researchers, containing information regarding indication, administration mode, adverse effects, storage, and other precautions for the listed oral antineoplastics: Anagrelide, Cyclophosphamide, Chlorambucil, Melphalan, Lomustine, Mercaptopurine, Methotrexate, Mitotane, Pazopanib, Sorafenib, Temozolomide, Thioguanine, Ruxolitinib, and Tretinoin; b) Validation of the developed materials through a median grade among experts in the field (oncology and/or hematology pharmacists), using the Delphi Method, evaluating layout and content through a Likert scale. Data dispersion was assessed through the interquartile range (IQR), and adequate grade was defined as a median above 3. Results: The educational pamphlets were developed using national and international references, encompassing necessary information for the adequate and safe use of medications by patients. The initial validation involved 19 pharmacists specialized in oncology and/or hematology, spread across the national territory. In the first evaluation round, there was disagreement among experts on two issues, both related to the material's content (highlighted sections and language used). After addressing points of disagreement, the pamphlets were validated by adequate grade among eight experts who remained in the study for the second round. Conclusion: It was possible to validate by experts the educational content of booklets containing written guidance on pharmacotherapy that will be delivered to the patient/caregiver, covering topics relevant to different medications, containing information with assertive scientific evidence, combining illustrations and language that is easy to understand by the population.